Effect of thermal oxidant stimulation on the alteration of shale seepage channel: Implication from the change of macromorphology and microstructure. (May 2023) - Liu, Danqing; Yang, Sen; Yi, Manling; Zhang, Yang; Yang, Zhe; Li, Yilian
Abstract: Alteration of the seepage channel through the shale-oxidant interactions is critical for using oxidant stimulation to enhance fluid mobility in tight shale reservoirs. Although many studies reported the effect of oxidant stimulation on the macro-crack morphology of shale, little is still known about its impact on shale microstructure, especially under reservoir temperature. In this study, we explored the influence of three oxidants, including H2 O2, NaClO and Na2 S2 O8, on the alteration of shale pores and fractures at reservoir temperature (60 °C), and illustrated the underlying mechanism based on water chemistry and solid characterization including X-ray diffraction, Fourier-transform infrared spectroscopy, low-pressure nitrogen gas adsorption, scanning electron microscopy coupled with energy dispersive spectroscopy analyses. Results showed that the reaction temperature and oxidant type both led to an inconsistent response of shale macromorphology and microstructure during oxidant stimulation. Three oxidants processed different shale matrix alteration, with the degree shown as follows: Na2 S2 O8  > H2 O2  > NaClO. Even though gas generated from the thermal and catalytic decomposition of H2 O2 and dissolution of carbonate were both favorable for the shale plug disintegration, the rapid consumption of H2 O2 limited the change of shale pore structure. After being treated with NaClO, the organic nanopores were transformed into larger mesopores and macropores with a decrease in pore surface roughness and structural complexity. Therefore, other methods should be combined with NaClO simulation to generate fractures and improve the fluid fluidity of shale. The serious dissolution and precipitation of minerals by Na2 S2 O8 causes significant alteration in the shale matrix, resulting in a large number of pores and induced fractures. Our research confirms the distinct effects of different oxidants on shale fractures and micropores, and the most promising Na2 S2 O8 for improving shale permeability, but still needs to be demonstrated by core-flooding experiments in the future. Highlights: Heat-decomposed H2 O2 slightly altered matrix but disintegrated shale. NaClO transformed the organic nanopores of shale into mesopores and macropores. Na2 S2 O8 severely altered shale matrix with abundant pores and induced fractures. Oxidant stimulation effect should focus more on microstructure rather than mass.